2018
DOI: 10.1002/jcb.28231
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA myocardial infarction–associated transcript regulated the pancreatic stellate cell activation to promote the fibrosis process of chronic pancreatitis

Abstract: Background: Long noncoding RNAs (lncRNAs) play crucial roles in fibrosis process. In our previous RNA-seq study, we found that lncRNA myocardial infarction-associated transcript (MIAT) was differentially expressed in pancreatic tissues of chronic pancreatitis (CP) patients. However, the function of MIAT in CP remains unknown. This study was aimed to investigate the function and underlying mechanism of MIAT in pancreatic fibrosis. Materials and Methods: The expression levels of MIAT, miR-216a-3p, cyclooxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Wang et al reported that the inhibition of syntaxin-12 lncRNA, which making miR-148a upregulated and Smad5 decreased, ultimately resulting in the suppression of PSC activation [60]. Liu et al had a similar discovery that lncRNA myocardial infarction-associated transcript contributed to PSCs activation through suppressing miR-216a-3pmediated COX-2, which finally leading to pancreatic fibrosis [61]. Same studies also uncover the inhibitory effect of miR-200a in PSCs activation [62].…”
Section: Non-coding Rnasmentioning
confidence: 98%
“…Wang et al reported that the inhibition of syntaxin-12 lncRNA, which making miR-148a upregulated and Smad5 decreased, ultimately resulting in the suppression of PSC activation [60]. Liu et al had a similar discovery that lncRNA myocardial infarction-associated transcript contributed to PSCs activation through suppressing miR-216a-3pmediated COX-2, which finally leading to pancreatic fibrosis [61]. Same studies also uncover the inhibitory effect of miR-200a in PSCs activation [62].…”
Section: Non-coding Rnasmentioning
confidence: 98%
“…[30][31][32] A large body of evidence from both animal and human studies demonstrate that the TGF-β signalling pathway mediates the progression of fibrotic processes. 29,33,34 Hic-5 was originally characterized as a TGF-βinducible gene. Our results indicate that quiescent PSCs exhibit extremely low expression levels of Hic-5, activation with TGF-β leads to a significant up-regulation of Hic-5 and knocking out Hic-5 did not alter the expression levels of TGF-β in our mice model of CP.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis of the pancreas sections indicated that the expression of α-SMA, a marker for activated PSCs, 29 was significantly decreased in the pancreas of Hic-5 KO mice treated with cerulein compared with the wild-type mice treated with cerulein ( Figure 4A). We evaluated the mRNA levels of fibrosis-associated and Timp1 in the pancreas of the Hic-5 KO mice were significantly lower than those of the wild-type mice, following cerulein treatment ( Figure 4B).…”
Section: Knockout Of Hic-5 Decreases the Expression Of Cerulein-indmentioning
confidence: 99%
See 2 more Smart Citations